Essentials of WMS-IV assessment - Drozdick, Lisa Whipple; Holdnack, James A.; Hilsabeck, Robin C. (Hoboken, N.J. : Wiley, 2011)
The most recent revision of one of the most popular memory assessment instruments, the Wechsler Memory Scale-Fourth Edition (WMS{uD256}) is a widely used measure of memory functioning, which is particularly useful in the assessment of individuals with dementia, traumatic brain injury, and substance abuse problems, among others. Professionals need an authoritative source on administration, scoring, and interpretation in order to use this test properly. Written by the test developers for the WMS{uD256}, Essentials of WMS{uD256} Assessment is that source.
Like all the volumes in the Essentials of Psychological Assessment series, this book is designed to help busy mental health professionals, and those in training, quickly acquire the knowledge and skills they need to make optimal use of major psychological assessment instruments. Each concise chapter features numerous callout boxes highlighting key concepts, bulleted points, and extensive illustrative material, as well as test questions that help you gauge and reinforce your grasp of the information covered.
Integrating WMS{uD256} data with the WAIS{uD256} and other measures of cognitive ability and memory for adults, Essentials of WMS{uD256} Assessment now includes four new subtests and a revised index structure. The authors also offer expert assessment of the test's relative strengths and weaknesses, valuable advice on its clinical applications, and several illuminating case studies. --Book Jacket.
Machine generated contents note: One. Overview -- Two. How to Administer the WMS-IV -- Three. How to Score the WMS-IV -- Four. Interpretation -- Five. Strengths and Weaknesses of the WMS-IV -- Six. Using WMS-IV with WAIS-IV -- Seven. Clinical Applications of the WMS-IV -- Eight. Illustrative Case Reports.
Includes bibliographical references and indexes.
Keywords: Wechsler Memory Scale; Memory -- Testing; Wechsler Scales; Memory